High PAE high reliability AlN/GaN double heterostructure. (November 2015) - Medjdoub, F.; Zegaoui, M.; Linge, A.; Grimbert, B.; Silvestri, R.; Meneghini, M.; Meneghesso, G.; Zanoni, E.
Abstract: We report on AlN/GaN double heterostructures for high frequency applications. 600 h preliminary reliability assessment has been performed on these emerging RF devices, showing promising millimeter-wave 100 nm gate length GaN-on-Si device stability for the first time. A 150 nm AlN/GaN double heterostructure has been developed and evaluated on SiC substrate. State-of-the-art CW power-added-efficiencies (PAE) up to 40 GHz have been achieved on ultrathin barrier (6 nm) GaN devices while operating at a drain bias exceeding 30 V.